2001
DOI: 10.1002/glia.10023
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic optical signals in the rat optic nerve: Role for K+ uptake via NKCC1 and swelling of astrocytes

Abstract: Measurements of extracellular space volume and imaging of intrinsic optical signals (IOSs) have shown that neuronal activity increases light transmittance by causing cellular swelling. However, the cellular mechanisms underlying these volume changes and the contribution of astrocyte swelling to the changes in tissue volume are unclear. In this study, we have investigated IOSs in optic nerves to analyze the mechanisms contributing to these signals in a system consisting of only axons and glial cells. We examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
132
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(142 citation statements)
references
References 48 publications
6
132
1
Order By: Relevance
“…One of the possible mediators is neuronally released K ϩ ; however, in contrast to previously described swelling-inducing effects of high extracellular K ϩ on glial cells (Walz and Hinks, 1985;Syková et al, 1999;MacVicar et al, 2002), we observed a fast and transient decrease of the thickness of glial cell processes (Fig. 7 A, B).…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…One of the possible mediators is neuronally released K ϩ ; however, in contrast to previously described swelling-inducing effects of high extracellular K ϩ on glial cells (Walz and Hinks, 1985;Syková et al, 1999;MacVicar et al, 2002), we observed a fast and transient decrease of the thickness of glial cell processes (Fig. 7 A, B).…”
contrasting
confidence: 99%
“…It occurred after longer incubation time periods (at least 1 hr) and is thought to be mediated by the Na ϩ transport that drives the uptake of glutamate (Izumi et al, 1996). Likewise, elevated extracellular K ϩ has been shown to cause astrocytic cell swelling (Syková and Orkand, 1980;Walz and Hinks, 1985;Anderova et al, 2001;MacVicar et al, 2002). Rapid glutamate-or K ϩ -evoked morphological alterations of retinal glial cells (i.e., thinning and elongation of stem processes) have never been described.…”
Section: Mechanism Of Glial Cell Morphological Alterationsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Specifically, furosemide antagonize the Na + -K + -2Cl -(NKCC1) cotransporter that is present on both neurons and glial cells, and the neuron-specific K + -Cl -(KCC2) cotransporter. 10,11 Furosemide has significantly greater affinity for NKCC1 over KCC2. 10 Hyperpolarizing inhibitory postsynaptic potentials in neurons are generated by the influx of anions (HCO3 -and Cl -) down their electrochemical gradients.…”
Section: Discussionmentioning
confidence: 99%
“…The probable mechanism of anxiolytic properties of Furosemide could be by enhancing GABA inhibition, causing antagonism of Na + -K + -2CL -and Na + -CL -cotransporters. [5][6][7][8][9][10] Further studies are required to explore the exact mechanism of action of anxiolytic effect of furosemide.…”
Section: Introductionmentioning
confidence: 99%